2017
DOI: 10.1002/jrs.5285
|View full text |Cite
|
Sign up to set email alerts
|

Raman‐scattering studies of pressure‐induced phase transitions in perovskite‐like acetamidninium manganese formate

Abstract: We report high‐pressure Raman scattering studies of acetamidninium manganese formate, which show evidence for two pressure‐induced phase transitions between 0.7 and 1.4 GPa and above 5.3 GPa. The first transition is related to distortion of the manganese formate framework whereas the second one affects significantly the structure of the acetamidinium cation. Significant narrowing of the lattice bands suggests that the intermediate and high‐pressure phases are ordered. High‐pressure experiments also indicate di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 40 publications
(107 reference statements)
2
19
0
Order By: Relevance
“…On the other hand, with the exception of the well-studied lead halide perovskite semiconductors [8][9][10], relatively few structural studies of materials in this family under applied pressure have been reported [11][12][13], although in some cases vibrational spectroscopy has intriguingly indicated structural changes [14,15]. In particular, spectroscopic methods have revealed high-pressure changes in many metal formate hybrid perovskites [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, with the exception of the well-studied lead halide perovskite semiconductors [8][9][10], relatively few structural studies of materials in this family under applied pressure have been reported [11][12][13], although in some cases vibrational spectroscopy has intriguingly indicated structural changes [14,15]. In particular, spectroscopic methods have revealed high-pressure changes in many metal formate hybrid perovskites [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…29,30 In particular, three transitions were identified for DMAMnF and DMAMgF (at 1.6(5), 3.7(5), and 5.9(9) GPa for DMAMnF and at 1.9(3), 3.7(3), and 5.4(3) GPa for DMAMgF), 29,30 and two transitions for DMACdF (at 1.6(4) and 3.5(1) GPa); 30 note that the average of the pressure points before and after the transition were employed, with the error indicating the pressure step. Many other spectroscopic studies have been carried out on related protonated-amine or ammonium metal formates that show transitions under compression, 5,[31][32][33][34][35][36] however few studies have investigated the structural distortions using diffraction. 37,38 Here we concentrate purely on the structural evolution with pressure, and study the […”
Section: Introductionmentioning
confidence: 99%
“…[191] Maczka and co-workers described Raman scattering of pressureinduced phase transitions in perovskite-like acetamidninium manganese formate. [192] Moshkina and co-workers observed temperature-dependent absorption lines in Raman spectra of SmFe 3 (BO 3 ) 4 ferroborate. [193] Petrov studied the Raman spectrum of ethane in a methane environment.…”
Section: Metals Carbons and Other Crystalline Materialsmentioning
confidence: 98%
“…Liu et al studied the unravelling of the decomposition products of phosphine under high pressure where it shows superconducting behaviour . Maczka and co‐workers described Raman scattering of pressure‐induced phase transitions in perovskite‐like acetamidninium manganese formate . Moshkina and co‐workers observed temperature‐dependent absorption lines in Raman spectra of SmFe 3 (BO 3 ) 4 ferroborate .…”
Section: High Pressure Temperature Studies Phase Transitions and Gmentioning
confidence: 99%